Pengaruh Word of Mouth dan Citra Perusahaan Terhadap Keputusan Penggunaan Jasa Ekspedisi JNE Express di Kabupaten Buleleng - Sari, Ni Ketut Megah Purnama; Mayasari, Ni Made Dwi Ariani (Universitas Pendidikan Ganesha, 2021)
This study was aimed to examine the effect of simultaneous and partially word of mouth and corporate image on use decisions of JNE Express Buleleng. The number of samples in this study were 100 respondents, the sample technique used purposive sampling. The data method used a questionnaire. The data analysis technique in this research is quantitative using multiple linear regression analysis. The result of the study showed that (1) word of mouth and corporate image has a positive and significant effect simultaneous on use decisions with a contribution influence of 83.7%. (2) Word of mouth has a positive and significant effect partially on use decisions with a contribution influence of 25.6%. (3) Corporate image has a positive and significant effect partially on with a use decisions contribution influence of 28.6%.